Teff and its role in the agricultural and food economy - Hassen, Ibrahim Worku; Regassa, Mekdim Dereje; Berhane, Guush; Minten, Bart; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2018)
The chapter first discusses the role of teff on the production side. Ethiopia is an extremely diverse country, with large variation in ecosystems and agricultural potential, ranging from pastoralist areas to moisture-reliable lowlands and highlands as well as drought-prone highlands and lowlands (Chamberlin and Schmidt 2012). Moreover, there is large variation in population density and access to markets. These factors contribute to a diversified agricultural economy with spatial specialization of agricultural activities and very diverse livelihood strategies. Next, the chapter analyzes teff consumption. Data are analyzed from national consumption surveys over a 15-year period to illustrate the extent to which transformation in consumption patterns is occurring (for an overview of patterns in nutritional transition in developing countries overall, see Popkin [2003]) and what exactly the role is of teff in Ethiopia’s changing food economy. To better understand that transformation, the link between food demand and income levels in particular is examined later in the chapter. This might give an indication of the trend in food consumption patterns, especially within a country where urbanization is encouraged and mid-income status is set as a goal by the year 2025 in several policy documents.